Reconstructing latin american history in walker and the mission: postmodernism and allegory - Anelise Reich Corseuil (Ilha do Desterro)
The controversies surrounding the term postmodernism suggest a number of differences in the production, aesthetics, and critical backgrounds involving the making of and writing about recent fictional texts. Postmodernist texts, filmic and literary, are characterized by the coexistence of different genres, the conjunction of both high and mass culture, and the representation of the historical past. Critics like Fredric Jameson and Guy Debord have questioned the validity of such historical representations, which are said to transform historical past into sources for stylistic forms and historical crisis into commodities to be easily consumed by audiences1. By contrast to the alleged ahistoricism of postmodernist representations, as defined by Jameson, in his article Ò“Third-World Literature in the Era of Multinational Capital,” thirdworld texts have been defined as “nationalist” or “allegorical.”2